Exposição à concentração subletal de metilmercúrio: genotoxicidade e alterações na proliferação celular - MALAQUIAS, Allan Costa (Universidade Federal do Pará, 2015)
Mercury is a metal that stands out from the rest for present liquid under normal temperature and pressure. This xenobiotic is the largest source of pollution in many parts of the world and has been characterized toxic to the central nervous system (CNS). After dumping in liquid form directly into soil and riverbed, this heavy metal complex with various organic elements or it is converted to methylmercury (MeHg) by aquatic microbiota. The MeHg can move up the food chain, an event known as biomagnification, which directly affects human life. Thereby, the Amazon stands out for having all the components necessary for the maintenance of biogeochemical cycle of mercury as well as populations chronically exposed with this heavy metal. And this metal is considered a public health problem. It is well known that this xenobiotic after acute exposure to high doses promotes disorders related to the emergence of degenerative processes in the CNS, however, the effects at low concentrations are not yet fully described. Despite this cell type play an important role in the mercury intoxication process, the role of this metal on glial cells is not well known, especially on the genome and cell proliferation. Thus, this study aimed to evaluate the effect of exposure to this xenobiotic at low concentration on DNA and cell proliferation in C6 glial lineage cells. The biochemical (mitochondrial activity - measured by MTT assay -) and morphofunctional evaluations (membrane integrity - measured by the assay with dyes and AA BE -) confirmed the absence of cell death after exposure to heavy metals in a concentration of 3 μM for 24 hours. Even without causing cell death processes, the treatment with sublethal concentration of MeHg that was able to significantly increase the levels of markers of genotoxicity (DNA fragmentation, micronuclei, nuclear nucleoplasmic bridges and nuclear bud). At the same time, it was possible to observe a change in the cell cycle by increasing the mitotic index and a change in the cell cycle profile with increased cell population in S and G2 / M phases, suggesting an arrest cell cycle arrest. This change in cell cycle caused by MeHg exposure was followed by number of viable cells and cell confluence decrease, 24 hours after the withdrawal of MeHg of culture medium. The C6 cell line culture in addition showed an increase on doubling time parameter. This study demonstrates for the first time exposure to methylmercury low and sublethal concentration can promote genotoxic events and disturbances in cell proliferation in glial cell origin.